Serum salusin-β levels as predictors of coronary artery disease in obese Egyptian women - Nearmeen M Rashad; Wesam M.R Ashour; Ghada M Samir; Hala G Abomandour (SpringerOpen, 2019)
Background Obesity is a growing health concern that has become an epidemic all over the world. Obesity is associated with coronary artery disease (CAD). Salusin-β is an endogenous bioactive peptide that accelerates inflammatory responses in vascular endothelial cells and increases oxidative stress. The objective of this study was to explore the potential roles of salusin-β in endothelial dysfunction in CAD. Also, we aimed to evaluate the association between salusin-β with severity of CAD in obese Egyptian women. Patients and methods This cross-sectional study enrolled 95 obese women who were classified into two groups: 58 patients without CAD and 37 patients without CAD. All patients were investigated using a 12-lead standard ECG, echocardiography, and coronary arteriography. Salusin-β levels were measured by enzyme-linked immunosorbent assay. Results Salusin-β levels were significantly higher in obese patients with CAD compared with patients without CAD. Salusin-β levels were positively correlated with cardiometabolic risks and severity of coronary occlusion. Serum salusin-β levels, high-sensitivity C-reactive protein, and BMI were independently correlated with CAD and BMI. Homeostatic model assessment of insulin resistance, high-sensitivity C-reactive protein, and uric acid were the main associated variables of serum salusin-β levels among other clinical and laboratory biomarkers. The diagnostic power of serum salusin-β levels in differentiating CAD from obese patients without CAD was highly sensitive (97.2%) and the specificity was 98.3%. Conclusion The higher levels of salusin-β levels in obesity, as well as CAD, were positively correlated with cardiometabolic risk factors and severity of coronary occlusion. Therefore, salusin-β levels seem to be a noninvasive biomarker of CAD.